EFFECT OF VITAMIN D SUPPLEMENTATION ON CLINICAL OUTCOMES IN CRITICALLY ILL ADULTS: A SYSTEMATIC REVIEW AND META-ANALYSIS OF RANDOMIZED CONTROLLED TRIALS WITH SUBGROUP ANALYSIS BY BASELINE VITAMIN D STATUS - Inri Eunike Sigarlaki; Salmawati Maryati (International Medical Journal Corp. Ltd, 2026)
Introduction: Vitamin D deficiency is highly prevalent among critically ill patients and has been associated with increased morbidity and mortality. Despite strong biological plausibility and supportive observational data, randomized controlled trials (RCTs) evaluating vitamin D supplementation in this population have yielded inconsistent results. This study aimed to systematically evaluate the effect of vitamin D supplementation on clinical outcomes, particularly mortality, in critically ill adult patients. Methods: A systematic review and meta-analysis of RCTs was conducted in accordance with PRISMA guidelines. Electronic databases (PubMed, Scopus, ScienceDirect, and Cochrane) were searched for studies published between January 2015 and December 2025. Eligible studies included RCTs involving adult critically ill ICU patients receiving vitamin D supplementation compared with placebo. The primary outcome was all-cause mortality. Secondary outcomes included ICU length of stay, hospital length of stay, and duration of mechanical ventilation. Pooled risk ratios (RRs) with 95% confidence intervals (CIs) were calculated using a random-effects model. Risk of bias was assessed using the Cochrane RoB 2 tool. Results: Five RCTs comprising 1,736 critically ill patients (871 in the intervention group and 865 in the control group) were included. Vitamin D supplementation was associated with a no statistically significant difference in mortality between groups (RR 0.74; 95% CI 0.53–1.05; p = 0.09). Substantial heterogeneity was observed (I² = 71.1%, p = 0.008), with a wide prediction interval (0.28–1.96). Larger trials demonstrated neutral effects, whereas smaller studies reported more pronounced benefits, suggesting a potential small-study effect. Secondary outcomes were inconsistently reported and showed variable findings, precluding quantitative synthesis. Discussion: The findings suggest that vitamin D supplementation does not provide a consistent mortality benefit in unselected critically ill populations. The observed heterogeneity, variation in study design, and potential influence of small-study effects contribute to the uncertainty of the overall estimate. While biological plausibility and subgroup signals indicate possible benefit in selected patients, current evidence remains insufficient to support routine use for mortality reduction. Conclusion: Vitamin D supplementation in critically ill adult patients was associated with a non-significant trend toward reduced mortality, with substantial heterogeneity across studies. Routine use of high-dose vitamin D for mortality reduction cannot be recommended based on current evidence. Further large-scale, well-designed trials focusing on clearly defined subgroups are needed.